Sie sind auf Seite 1von 10

For all applicable angles θ,

cos2θ – sin2θ
cos 2θ = 2cos2θ -1
1 – 2sin2θ

sin 2θ = 2sinθ cosθ

2tanθ
tan 2θ =
1 – tan2θ
5 3π
Given cos(θ) = , < θ < 2𝜋 , find sin(2θ), cos(2θ) and tan(2θ).
13 2

θ is in quadrant IV

2tan(θ)
cos(2θ) = 2cos2(θ) -1 sin(θ) = − 1− cos2(θ) tan(2θ) =
1 – tan2(θ)
2 sin(θ)
5 2 5 tan(θ) = cos(θ)
=2 -1 =− 1−
13 13
− 12
=
50
-1 12 = 13 = - 12
169 =-
13 5 5
13
119
cos(2θ) = -
169
sin(2θ) = 2sin(θ)cos(θ) 2 −12
12 5 5
=2 − tan(2θ) = 2
13 13 1 – 12
5
120
sin(2θ) = -
169 120
tan(2θ) =
119
Suppose P(-3, 4) lies on the terminal side of θ when θ is
plotted in standard position. Find cos(2θ) and sin(2θ) and
determine the quadrant in which the terminal side of the angle
2θ lies when it is plotted in standard position.

5
4
θ cos(2θ) = 2cos2(θ) -1 sin(2θ) = 2sin(θ)cos(θ)
2
-3 −3 4 3
cos(2θ) = 2 -1 =2 −
5 5 5
7 24
cos(2θ) = − sin(2θ) = -
4 25 25
sin(θ) =
5
3 2θ lies in Quadrant III since both
cos(θ) =− cosine and sine of 2 are negative.
5
Verify the identity: Develop a formula for cot (2θ) in
terms of θ.
2tan(θ)
sin(2θ) =
1 + tan2(θ) 1
cot (2θ) =
tan (2θ)
2tan(θ)
=
sec2(θ) 2tan(θ)
tan(2θ) =
1 − tan2(θ)
2 · sin(θ)
cos(θ) 1 − tan2(θ)
= cot (2θ) =
1 2tan (θ)
cos2(θ)
1 1
sin(θ) = − tan(θ)
=2 · · cos2(θ) 2 tan (θ)
cos(θ)
1
= 2sin(θ)cos (θ) = cot(θ) − tan(θ)
2

sin(2θ) = sin(2θ)
Express cos(3θ) as a polynomial in terms of cos(θ).

cos(3θ) = cos(2θ + θ)

= cos(2θ) cos(θ) - sin(2θ) sin(θ)


cos(2θ) = 2cos2(θ) - 1
sin(2θ) = 2sin(θ)cos(θ)

= 2cos2(θ) − 1 cos(θ) -
2sin(θ)cos(θ) sin(θ)
= 2 cos3(θ) - cos(θ) - 2 sin2(θ) cos(θ)
sin2 A + cos2A = 1

= 2 cos3(θ) - cos(θ) - 2 1− cos2A cos(θ)

= 2 cos3(θ) - cos(θ) – 2cos(θ) + 2 cos3(θ)

cos(3θ) = 4 cos3(θ) - 3cos(θ)


Establish the following identity using double-angle formulas:

1 + sin(2θ) = (sinθ + cosθ)2


= sin2θ + 2sinθcosθ + cos2θ sin2 A + cos2A = 1

= 1 + 2sinθcosθ sin(2θ) = 2sin(θ)cos(θ)

1 + sin(2θ) = 1 + sin(2θ)

2
= tan(2θ)
cot(θ) − tan(θ)
1
2tan(θ) tan(θ) 2
= · =
1 − tan2(θ) 1 1 − tan2(θ)
tan(θ) tan(θ) tan(θ)
2
=
cot(θ) − tan(θ)
2
= tan(2θ)
cot(θ) − tan(θ)

2
1 = tan(2θ)
− tan(θ)
tan (θ)
2
= tan(2θ)
1− tan2(θ)
tan (θ)

2tan(θ)
= tan(2θ)
1 − tan2(θ)

tan(2θ) = tan(2θ)
QUIZ

I. Given sec(θ) = 5 where < θ < 2𝜋 , find sin(2θ), cos(2θ) and
2
tan(2θ).

II. Establish the following identity using double-angle formulas:

cot(θ) + tan(θ)
csc(2θ) =
2